La perlesía y otras patologías neurológicas en El Quijote de Cervantes. - MEJÍA-RIVERA, ORLANDO (Acta Medica Colombiana)
Miguel de Cervantes had seasoned knowledge of medical care in his time. Here we provide evidence of his having read medical texts from his personal library and of his relationships with relatives and friends who were physicians. As an example of his knowledge, we analyze the references to palsy and other neurological diseases like epilepsy, tremors and head trauma, which are mentioned or described in his great literary masterpiece titled The Ingenious Gentleman Don Quixote.